2015
DOI: 10.1016/j.atmosenv.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

An AIS-based approach to calculate atmospheric emissions from the UK fishing fleet

Abstract: h i g h l i g h t sAn AIS-based emissions calculation methodology for fishing vessels is introduced. Fuel-and AIS-activity-based emissions inventories for a fishing fleet are compared. Trawling and dredging vessels have complex engine loads that must be simulated. Using AIS data allows greater flexibility when aggregating and mapping emissions. AIS-based methods produce higher emissions estimates than fuel-based methods. a b s t r a c tThe fishing industry is heavily reliant on the use of fossil fuel and emits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 20 publications
(26 reference statements)
0
35
0
Order By: Relevance
“…Scope 3 covers a diverse group of major emitters (e.g., port employees, tenants, trains, trucks, and ships) with low issue visibility. Scope 3 is defined in different ways by the five ports (Table 3) Identification System (AIS), which tracks the movements of individual ships in real-time, can also provide future opportunities to estimate GHG emissions from individual ships (Miola et al, 2011;Goldsworthy and Goldsworthy, 2015;Coello et al, 2015). All our port interviewees welcome higher emission visibility, arguing that transparency will facilitate further environmental upgrading.…”
Section: Tool Implementation Complexity and Emission Visibilitymentioning
confidence: 99%
“…Scope 3 covers a diverse group of major emitters (e.g., port employees, tenants, trains, trucks, and ships) with low issue visibility. Scope 3 is defined in different ways by the five ports (Table 3) Identification System (AIS), which tracks the movements of individual ships in real-time, can also provide future opportunities to estimate GHG emissions from individual ships (Miola et al, 2011;Goldsworthy and Goldsworthy, 2015;Coello et al, 2015). All our port interviewees welcome higher emission visibility, arguing that transparency will facilitate further environmental upgrading.…”
Section: Tool Implementation Complexity and Emission Visibilitymentioning
confidence: 99%
“…Two of the thirteen vessel types (see Section 3.1) were excluded from the analysis: (i) fishing vessels and (ii) others. Fishing vessels, such as trawlers tow fishing gears, which results in high engine loads at relatively low speeds (Coello et al, 2015). Therefore, low speeds do not necessarily translate into low engine power for these vessels.…”
Section: Step 1: Selecting Vessel Typesmentioning
confidence: 99%
“…Several studies estimate emissions of air pollutants from shipping (Buhaug et al, 2009;Coello et al, 2015;Goldsworthy and Goldsworthy, 2015;Skjølsvik et al, 2000;Smith et al, 2014;Winther et al, 2014). These studies follow either one or a combination of two approaches, both of which rely on estimating fuel consumption.…”
Section: Introductionmentioning
confidence: 99%
“…With this, it is possible to obtain the navigation information of ships in an accurate and quantitative manner. The AIS is required to be installed aboard all international voyaging ships larger than 300 gross tonnage (GT), all noninternational voyaging ships larger than 500 GT, and all passenger ships (IMO, 2003 As it is possible to observe the ship navigation information more easily and quickly, AIS data have been used in maritime research such as the investigation of traffic flow (Olindersson F et al, 2015), environmental pollution survey (Coello J. et al, 2015), and so on. Makino (2012) and Gao et al (2013) have shown that the analysis of historical ship navigation record using AIS data can reveal the characteristics of actual ship movement.…”
Section: Application Of Ais Datamentioning
confidence: 99%